Outcome Following Decompressive Craniectomy in a Tertiary Care Center in Nepal - Gurung, Ashim; Karki, Anjan Singh; Shrestha, Dipendra Kumar; Rajbhandari, Binod; Pradhanang, Amit B; Sedhain, Gopal; Shilpakar, Sushil Kumar; Sharma, Mohan Raj (Journal of Society of Surgeons of Nepal, 2021)
Introduction: Decompressive Craniectomy (DC) is a common neurosurgical procedure performed to reduce the intractable intracranial pressure in various neurosurgical diseases (infarction, hemorrhage, traumatic brain injury). The main aim of the study was to describe the demographic, clinical and operative characteristics of patients who underwent DC for different conditions and to correlate the outcome with various preoperative and intraoperative factors in our center. Methods: This was a retrospective study of patients who underwent DC for various neurosurgical diseases from January 2019 to January 2021 in Tribhuvan University Teaching Hospital, Kathmandu, Nepal. The chart of the patients were retrieved from the medical records and additional information obtained via telephone. Results: A total of 55 patients were enrolled in the study with a mean age of 43.0 + 17.3 years and male:female ratio of 1.5:1. There were 20 (36.4%) patients who presented with trauma and 35 (63.6%) patients with non traumatic origin. Among them, 28 (51%) patients presented with GCS<8 and 27 (49%) patients with GCS>8 and 37 (67.3%) patients with unequal pupil. At the end of six months follow up, the favorable outcome was seen in 23 (41.8%) patients. The only factor significantly associated with favorable outcome was the preoperative pupillary status. Conclusion: In our cohort the preoperative pupillary status (bilateral equal and reactive pupil) was the variable significant for favourable outcome in patients undergoing DC.